Acquisition of #sC clusters in Croatian speaking children - Mildner, Vesna; Tomić, Diana (2008)
The aim of this study was to examine the developmental patterns of #sC clusters and how these productions relate to the sonority sequencing principle. Data were collected form 35 typically developing Croatian speaking children, ages 1 ; 11 and 4 ; 2 in a picture-naming task combined with a sentence completion tasks. Target words consisted of complex onsets including #sC clusters. The analyzed patterns were the correct realizations of target clusters and the responses with cluster reductions. The results demonstrated great individual differences in the correct realizations of #sC clusters and limited support of the SSP for /s/+obstruent clusters and /s/+sonorant clusters.
Projekt MZOS
ENG